Uji Sinergitas Rendaman Tembakau (Nicotiana tabacum L.) dengan Jamur Trichoderma spp. Secara In Vitro dan Potensinya Sebagai Gabungan Biopestisida Alami - Nura Khabita; Indah Sulistiyawati; Ari Dwi Nurasih (Universitas Batanghari Jambi, 2022)
Management of plant pests and diseases can prevent crop failure of agricultural commodities. Trichoderma spp. is a type of biological control fungus. Tobacco can be used as a vegetable pesticide. However, the synergy of tobacco and Trichoderma spp. when applied simultaneously in controlling pathogens is not yet known, considering the content of the active compound nicotine in tobacco which has antifungal properties, it is necessary to conduct this study with the aim of knowing the effect of tobacco immersion on the growth of the fungus Trichoderma spp. and if there is no inhibition then both will have the potential as a combination of natural biopesticides. This study used a completely randomized design (CRD). The treatment tried was different concentrations of tobacco soak mixed with PDA as a culture medium for Trichoderma spp. The concentrations tested were 0% (T0, positive control), 5% (T1), 10% (T2), 15% (T3), and 20% (T4). The negative control used a fungicide with the active ingredient mankozeb. Each treatment was repeated 3 times. Colony thickness and color data were observed visually by descriptive method. Meanwhile, data on colony diameter, number of spores, dry weight of mycelium were analyzed by F test, if significantly different, then followed by DMRT test with a confidence level of 5%. Based on research that has been carried out from July-August 2021, the results obtained on PDA media with tobacco soaking content with concentrations of 0% (K+), 5% (T1), 10% (T2), 15% (T3), 20% (T4 ) can be grown with Trichoderma spp., while the media with the addition of synthetic fungicides made from mankozeb is not grown. The difference in concentration showed different growth results and the effective concentration in this research was 15%, because at 20% concentration there was a decrease in spore density and mycelium dry weight.